Global Financial Crisis: Did Exchange Rate Politics Help Emerging Countries To Be More Resilient? - Ouerghi, Feryel (International Journal of Economics and Financial Issues, 2013)
In this paper, we try to explain how exchange politics help emerging economies to escape global financial crisis. We conduct a comparative analysis between two periods: financial crises period of the 1990’s and global financial crisis of 2007-2008. We attempt to outline the determinants of a successful exchange rate regime choice. The study is based on traditional analysis of exchange rate regime choice (Optimum Currency Area theory and financial integration approach) and on political economy approach. The results show that resilience to crisis in emerging countries is improved by the choice of adequate exchange rate regime. Greater trade openness, higher economic integration, low inflation and democratic institutions which are associated with faster recovery, are the principal determinants of exchange regime during the period of 2005-2010. Keywords: Global crisis; exchange politics; currency crisis; exchange rate determinants. JEL Classifications: D72; F33; F41